Analisis Produksi Pesan Sosial Dengan Pendekatan Komedi Kearifan Lokal Pada Progam Televisi Publik ‘Angkringan’ - Joe Harrianto Setiawan; Daniari Setiawati; Heidy Isabel (Avant Garde, 2023)
TVRI, a public broadcasting service has the task of providing an information, education and entertainment services, control and streghthen community, and preserving the local wisdom. However, the existence of television in the internet era was disrupted by social media, thus TVRI had to change in presenting quality and educative information. TVRI Yogyakarta Youtube channel one of its flagship programs ‘Angkringan’ that able to reap millions of viewers. This research intends to find the social messages production process with local wisdom comedy of ‘Angkringan'. The television production process is divided into; pre-production consists of finding ideas, planning and preparation, then production and lastly post-production. Using descriptive qualitative research to produce systematic, factual, and accurate records about the facts and characteristic of certain activities. The results showed a pattern using local wisdom comedy namely Dagelan Mataram to produce social messages in ‘Angkringan’ program. The story’s idea is related to actual problems context. The script is made for open improvement with dialogue left entirely to player's improvisation. The players selection is carried out professionally but relationship between players maintained in like-family manner. The performance involves the audience on the stage to make it easier for improvisation as well as to measure the success.